A Review on Graphene-Based Nanomaterials in Biomedical Applications and Risks in Environment and Health - Shareena, Thabitha P. Dasari; McShan, Danielle; Dasmahapatra, Asok K.; Tchounwou, Paul B. (Nano-Micro Letters, 2018)
Graphene-based nanomaterials (GBNs) have attracted increasing interests of the scientific community due to their unique physicochemical properties and their applications in biotechnology, biomedicine, bioengineering, disease diagnosis and therapy. Although a large amount of researches have been conducted on these novel nanomaterials, limited comprehensive reviews are published on their biomedical applications and potential environmental and human health effects. The present research aimed at addressing this knowledge gap by examining and discussing: (1) the history, synthesis, structural properties and recent developments of GBNs for biomedical applications; (2) GBNs uses as therapeutics, drug/gene delivery and antibacterial materials; (3) GBNs applications in tissue engineering and in research as biosensors and bioimaging materials; and (4) GBNs potential environmental effects and human health risks. It also discussed the perspectives and challenges associated with the biomedical applications of GBNs. Highlights: 1 Structures and properties of graphene-based nanomaterials (GBNs) including graphene, graphene oxide (GO), reduced graphene oxide (RGO) and modified graphene are introduced briefly. 2 Recent advances in GBNs for the biomedical applications in drug delivery, biosensor, bioimaging and tissue engineering are summarized and analyzed. 3 Potential risks resulted from the vast production and applications of GBNs to the environment and health are discussed to ensure sustainable development of GBNs.